INSTITUTIONAL ASPECTS OF INNOVATIVE DEVELOPMENT IN UKRAINE: INTERNATIONAL COMPARISONS AND REGIONAL FEATURES: Array - Ostrovskyi, I. (Municipal economy of cities. Series: «Economy science», 2019)
The innovative component should be decisive in substantiating the strategic scientific and production priorities of the development of the state and its regions. The art of state administration regarding the distinction between current short-term and main long-term goals is evaluated based on the results of innovative development. This is the basis for the socio-economic progress of society. At the same time, innovation processes depend heavily on the institutional environment and a set of relevant institutional changes. Insensitivity to innovation processes in Ukraine is due to significant macroeconomic constraints: demographic negatives, decreasing scale of the country's economy, progressive deindustrialization, high resource-intensive production, low energy efficiency, and growing debt burden. The most destabilizing role is played by war events in the East. The scale of the national economy of Ukraine critically limits the importance and international competitiveness of the state and its regions. The main problem of innovation is the political and economic institutions of Ukrainian society, the asymmetry of economic power and the existing economic order. The benefits of economic power to the rental path of maximizing income are the cost for an innovative way. Therefore, the institutionalization of innovation development is a prerequisite for modern structural changes. The significance of regional subsystems in the complex of innovative development of the state's economy in the world is steadily increasing. Under the influence of globalization and integration processes in the European countries a paradigm of new regionalism is formed. This is confirmed by the functioning of the institutes that promote regional integration and cooperation of regions. The formation of a new regionalism causes the legal, economic and organizational conditions for the functioning of the subjects of the regions, the regulation of relations between them. To overcome the inconsistency of the industrial and institutional structures of society and to solve the problems of accelerated diversification of the structure of the regional economy, we must act on two models: 1) forcing traditional industrial production and services to meet the needs of end users; 2) ensuring the competitiveness of national enterprises in the context of the transition to a post-industrial economy. According to the second model, the value added is due to the high quality of human capital and the predominant use of intellectual resources.